P37 Convergent somatic mutations in effectors of insulin signalling in chronic liver disease. (28th September 2020) - Ng, Stanley; Brunner, Simon; Brzozowska, Natalia; Aitken, Sarah; Abascal, Federico; Moore, Luiza; Leongamornlert, Daniel; Ivovic, Aleksandra; Robinson, Philip; Butler, Timothy; Sanders, Mathijs; Williams, Nicholas; et al.
Abstract : Chronic liver disease is associated with metabolic dysregulation, liver failure and hepatocellular carcinoma. We analysed somatic mutations from 1202 genomes across 32 liver samples, including normal controls, alcohol-related and non-alcoholic fatty liver disease. Five of 27 patients with liver disease carried hotspot driver mutations in FOXO1, the major transcription factor downstream of insulin signalling. FOXO1 mutations were independently acquired by up to 5 distinct clones within the same patient's sample, and impaired insulin-mediated nuclear export of FOXO1. GPAM, which produces storage triacylglycerol from dietary calories, also had significant excess of mutations, similarly exhibiting convergent evolution within biopsies. Telomeres were shorter in diseased than normal liver, with attrition more pronounced in larger clones. Multiple independent acquisitions of drivers within one small liver sample imply that such mutations could affect hundreds of grams of tissue across the whole organ, potentially contributing to systemic metabolic dysfunction.